2020
DOI: 10.7717/peerj.10467
|View full text |Cite
|
Sign up to set email alerts
|

The performance of a modified EWMA control chart for monitoring autocorrelated PM2.5 and carbon monoxide air pollution data

Abstract: PM2.5 (particulate matter less than or equal to 2.5 micron) is found in the air and comprises dust, dirt, soot, smoke, and liquid droplets. PM2.5 and carbon monoxide emissions can have a negative impact on humans and animals throughout the world. In this paper, we present the performance of a modified exponentially weighted moving average (modified EWMA) control chart to detect small changes when the observations are autocorrelated with exponential white noise through the average run length evaluated (ARLs) by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…( 22) then the absolute percentage relative error named APRE(%) show that Eq. (24). It showed that the ARL values derived from the explicit formulas give results close to those from the NIE method both AR(2) and AR(3) process.…”
Section: Numerical Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…( 22) then the absolute percentage relative error named APRE(%) show that Eq. (24). It showed that the ARL values derived from the explicit formulas give results close to those from the NIE method both AR(2) and AR(3) process.…”
Section: Numerical Resultsmentioning
confidence: 65%
“…Karoon et al [23] developed the numerical integral equation (NIE) methods for evaluating the ARL on Extended EWMA chart for AR(p) process. Supharakonsakun et al [24] presented the exact average run length based on explicit formula the observations are from moving average process with exponential white noise for modified EWMA chart. Phanthuna et al [25] proposed the explicit formula for evaluating the ARL on a two-sided modified EWMA chart under the observations of AR(1) process.…”
Section: Introductionmentioning
confidence: 99%
“…charts and examples of their use with correlated data, see Hunter (1986); Lucas and Saccucci (1990); Supharakonsakun et al (2020).…”
Section: Detection Of Trend Deviationsmentioning
confidence: 99%
“…Explicit formulas for the exact ARL were provided and their accuracy was compared with the NIE method. Supharakonsakun et al [32] suggested explicit formulas for the ARL with observations from a MA model on the modified EWMA control chart and compared their capability with the same process on the standard EWMA scheme for monitoring PM2.5 and carbon monoxide air pollution data; their results show that the modified EWMA control chart was much better at detecting shifts in the process parameter than the standard EWMA control chart. Supharakonsakun [33] designed the modified EWMA control chart for a seasonal MA model and evaluated its efficacy by using the ARL calculated via explicit formulas and the NIE method.…”
Section: -Literature Reviewmentioning
confidence: 99%